Vanadio-oxy-dravite, NaV3(Al4Mg2)(Si6O18)(BO3)3(OH)3O, a new mineral species of the tourmaline supergroup - BOSI, Ferdinando; H. Skogby; L. Reznitskii; U. Halenius (American Mineralogist, 2014)
Vanadio-oxy-dravite, NaV3(Al4Mg2)(Si6O18)(BO3)(3)(OH)(3)O, is a new mineral of the tourmaline supergroup. It is found in metaquartzites of the Pereval marble quarry (Sludyanka, Lake Baikal, Russia) in association with quartz, Cr-V-bearing tremolite and mica, diopside-kosmochlor-natalyite, Cr-bearing goldmanite, escolaite-karelianite, dravite-oxy-vanadium-dravite, V-bearing titanite and rutile, ilmenite, oxyvanite-berdesinskiite, shreyerite, plagioclase, scapolite, zircon, pyrite, and an unnamed oxide of V, Cr, Ti, U, and Nb. Crystals are green, transparent with a vitreous luster, pale green streak, and conchoidal fracture. Vanadio-oxy-dravite has a Mohs hardness of approximately 7 1/2, and a calculated density of 3.14 g/cm(3). In plane-polarized light, vanadio-oxy-dravite is pleochroic (O = yellow green and E = pale olive green) and uniaxial negative: omega = 1.693(5), epsilon = 1.673(5). Vanadio-oxy-dravite is rhombohedral, space group R3m, with the unit-cell parameters a = 16.0273(3), c = 7.2833(1) angstrom, V = 1620.24(5) angstrom(3), Z = 3. Crystal-chemical analysis resulted in the empirical structural formula: (X)(Na0.70Ca0.23 square K-0.05(0.02))(Sigma 1.00) (Y)(V1.393+Mg1.16Al0.35Fe0.043+Ti0.044+Fe0.022+)(Sigma 3.00) (Z)(Al3.74Mg1.28V0.783+Cr0.203+)(Sigma 6.00) (T)(Si6.00O18) (B)(BO3)(3) (v)(OH)(3) (W)[O-0.74(OH)(0.26)](Sigma 1.00). The crystal structure of vanadio-oxy-dravite was refined to an R1 index of 1.70% using 1800 unique reflections collected with MoK alpha X-radiation. Ideally, vanadio-oxy-dravite is related to oxy-dravite and oxy-vanadium-dravite by the homovalent substitution V3+<-> Al3+. Tourmaline with chemical compositions classified as vanadio-oxy-dravite can be either Al dominant or V dominant as a result of the compositional boundaries along the solid solution between Al and V3+ that are determined at (Y+Z)(V1.5Al5.5), corresponding to Na-Y(V1.5Al1.5)(Z)(Al4Mg2)Si6O18(BO3)(3)(OH)(3)O, and (Y+Z)(V5Al2), corresponding to Na-Y(V-3)(Z)(V2Al2Mg2)Si6O18(BO3)(3)(OH)(3)O.